Intestinal Anti-Inflammatory Activity of Terpenes in Experimental Models (2010-2020): A Review - Araruna, Maria Elaine; Serafim, Catarina; Alves Junior, Edvaldo; Hiruma-Lima, Clelia [UNESP]; Diniz, Margareth; Batista, Leonia (Mdpi, 2020)
Inflammatory bowel diseases (IBDs) refer to a group of disorders characterized by inflammation in the mucosa of the gastrointestinal tract, which mainly comprises Crohn's disease (CD) and ulcerative colitis (UC). IBDs are characterized by inflammation of the intestinal mucosa, are highly debilitating, and are without a definitive cure. Their pathogenesis has not yet been fully elucidated; however, it is assumed that genetic, immunological, and environmental factors are involved. People affected by IBDs have relapses, and therapeutic regimens are not always able to keep symptoms in remission over the long term. Natural products emerge as an alternative for the development of new drugs; bioactive compounds are promising in the treatment of several disorders, among them those that affect the gastrointestinal tract, due to their wide structural diversity and biological activities. This review compiles 12 terpenes with intestinal anti-inflammatory activity evaluated in animal models and in vitro studies. The therapeutic approach to IBDs using terpenes acts basically to prevent oxidative stress, combat dysbiosis, restore intestinal permeability, and improve the inflammation process in different signaling pathways.
Keywords: terpenes; intestinal anti-inflammatory; ulcerative colitis; cytokines; natural products